Genomic Characterization of Two Escherichia fergusonii Isolates Harboring mcr-1 Gene From Farm Environment - Liu, Ruishan; Xu, Hao; Guo, Xiaobing; Liu, Shuxiu; Qiao, Jie; Ge, Haoyu; Zheng, Beiwen; Gou, Jianjun (Frontiers in Cellular and Infection Microbiology, 2022)
The prevalence and transmission of mobile colistin resistance (mcr) genes have led to a severe threat to humans and animals. Escherichia fergusonii is an emerging pathogen, which is closely related to a variety of diseases. However, the report of mcr genes harboring E. fergusonii is still rare. One study in Brazil reported the E. fergusonii isolates with IncHI2-type plasmids harboring mcr-1. A Chinese study reported two strains carrying mcr-1 gene with the same plasmid type IncI2. Here, we identified two strains of E. fergusonii carrying mcr-1 gene from farm environments with IncX4-type and IncI2-type plasmids, respectively. To our best knowledge, this is the first report about mcr-1 gene located on IncX4-type plasmid in E. fergusonii. We investigate the resistance mechanism of colistin-resistant Escherichia fergusonii strains 6S41-1 and 5ZF15-2-1 and elucidate genetic context of plasmids carrying mcr-1 genes. In addition, we also investigated chromosomal mutations mediated colistin resistance in this two strains. Species identification was performed using MALDI-TOF MS and 16S rRNA gene sequencing. The detection of mcr-1 gene was determined by PCR and Sanger sequencing. S1-pulsed-field gel electrophoresis (PFGE), Southern blotting, antimicrobial susceptibility testing, conjugation experiments, complete genome sequencing, and core genome analysis was conducted to investigate the characteristics of isolates harboring mcr-1. The mcr-1 genes on two strains were both plasmids encoded and the typical IS26-parA-mcr-1-pap2 cassette was identified in p6S41-1 while a nikA-nikB-mcr-1 locus sites on the conjugative plasmid p5ZF15-2-1. In addition, Core genome analysis reveals that E. fergusonii 6S41-1 and 5ZF15-2-1 have close genetic relationships. The mcr-1 gene located on conjugative IncI2-type plasmid p5ZF15-2-1, which provides support for its further transmission. In addition, the possibility of mcr-1 may spread to humans through farm environments and thereby threaten public health. Therefore, continuous monitoring and investigations of mcr-1 among Enterobacteriaceae in farm environments are necessary in the future.